The use of negative pressure therapy in a patient with a pressure injury in the sacral region: a case report (Research, Society and Development, 2022)
Negative Pressure Therapy (NPT) is an adjunctive treatment that uses a suction force on the wound bed between 20 to 120 mmHg, favoring granulation, decreased edema, reduced local bacterial load, increased local blood flow , reduces pain, favoring an ideal local microclimate for healing. Objective: To report a clinical case of a patient who had a pressure injury in the sacral region, submitted to negative pressure therapy. Method: Research carried out in a clinic specialized in prevention and comprehensive treatment of wounds, from which the evolution of a clinical case was reported, available in an adult patient's chart, with pressure injury in the sacral region. This is a qualitative study of the case report type, being a descriptive and explanatory research, as it reports a therapy used by a patient who obtained positive results, through the medical record, interview with the patient and photographic record of the diagnostic methods to which the patient was submitted. The research was submitted to the Research Ethics Committee of Faculdade Independente do Nordeste – FAINOR and conducted in accordance with Resolution No. 466/2012 of the National Health Commission. Results and Discussion: As a consequence of the prolonged hospitalization, the patient developed a LPP in the sacral region, with a deep bed, evolving positively with the use of NPT. Final considerations: The use of negative pressure therapy as an important alternative in the treatment of pressure injuries that are difficult to heal.